PENGARUH PDRB, UPAH MINIMUM, PENGANGGURAN TERBUKA DAN INDEKS PEMBAGUNAN MANUSIA TERHADAP JUMLAH PENDUDUK MISKIN DI KABUPATEN/KOTA PROVINSI SUMATERA UTARA - Karimi, Kasman; Nasution, Indah (Jurnal Ekonomi Sakti, 2024)
This study aims to see how the effect of Economic Growth, District/City Minimum Wage, Open Unemployment Rate and Human Development Index on the Number of Poor People in North Sumatra Province. The data analysis method used is panel data (time series and cross section) from 33 regencies/cities of North Sumatra province for 5 years from 2017 to 2021. The data analysis technique uses a panel regression model through 3 approaches, namely CEM, FEM and REM. The results of the selected model Fixed Effect study show that Economic Growth (GRDP), and the Regency/City Minimum Wage (UMK) are negatively and significantly related to the number of poor people in North Sumatra Province, while the variables Open Unemployment Rate and Human Development Index (HDI) have a significant positive effect on the number of poor people in North Sumatra Province.